Sodium-ion battery electrolyte as well as preparation method and application thereof
By using electrolyte composed of conductive sodium salt, organic solvent and composite additives in sodium ion batteries, the problem of low stability of traditional electrolyte under high voltage conditions is solved, and an electrolyte with high conductivity, low cost and high cycle stability is achieved. It is suitable for sodium ion batteries above 4V.
Patent Information
- Application Number
- CN202311261445.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
In sodium ion batteries, the stability of traditional electrolytes under high voltage conditions is low, resulting in poor circulation performance, which seriously restricts the commercial application of phosphate-based cathode materials.
An electrolyte consisting of conductive sodium salt, organic solvent and composite additives is used, including nitriles, sulfonate esters and organic sodium salts. The total mass concentration of the composite additive is 2 wt%-10 wt% to improve the stability and conductivity of the electrolyte.
The electrolyte generates a dense SEI layer rich in inorganic components, ensuring the rapid diffusion of Na+ ions, reducing the organic content in SEI, improving the stability of SEI during long-term cycles, and the capacity retention rate of 1,000 cycles at a 1C ratio is greater than 80%.
Smart Images

Figure SMS_1 
Figure HDA0004473078050000011
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery electrolyte, a preparation method and application thereof. Background Art
[0002] As industries such as transportation and digital technology become increasingly dependent on lithium-ion batteries, the shortage of lithium resources has begun to restrict their development. Sodium has similar properties to lithium, and is abundant and relatively cheap. Sodium-ion batteries have the advantages of good safety performance, low price, and high specific energy, and are expected to develop into an energy storage technology with great application potential. Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low cost and high safety.
[0003] In the battery system, the electrolyte, as the medium of electrochemical reaction, is an important component of the battery and a key factor in determining the thermodynamic and kinetic processes of the interfacial reaction of the electrode material, thus affecting the cycle stability and rate performance of the sodium-ion battery.
[0004] In sodium-ion batteries, phosphate-based cathode materials have the advantages of fast ion conduction speed and stable structure, and are an important raw material for sodium-ion batteries. Among them, cathode materials such as sodium vanadium fluorophosphate and sodium manganese vanadium phosphate have a charge and discharge voltage platform of more than 4V, which gives the battery a higher capacity. The corresponding energy density is expected to be comparable to that of lithium iron phosphate batteries. For example, batteries based on sodium vanadium fluorophosphate have a charge and discharge voltage platform of more than 4V. + / Na) has a high voltage platform, and the specific energy of the battery exceeds 140Wh kg -1 However, when the cathode potential exceeds 4.2 V, the conventional electrolyte commonly used at present is not stable enough under high voltage, resulting in poor cycle performance, which seriously restricts the commercial application of this type of cathode material.
[0005] In order to solve the problem of low electrolyte stability under the above-mentioned high voltage conditions, researchers have proposed strategies of high-concentration electrolyte and local high-concentration electrolyte this year. High-concentration electrolyte can not only increase the oxidative stability of the electrolyte itself, but also increase the proportion of coordinated contact ion pairs (CIPs) and ion aggregates (AGGs) in the electrolyte solvation structure, which is conducive to the formation of SEI and CEI rich in inorganic components. These advantages of high-concentration electrolyte significantly improve the cycle stability of sodium-ion batteries. However, in high-salt systems, as the concentration increases, the interaction force between anions and cations will also increase, and the increase in electrolyte viscosity will lead to a decrease in ionic conductivity, thereby making the wettability of the electrolyte to the electrode worse, that is, the interfacial compatibility worse. At the same time, the increase in the use of conductive sodium salt will increase the cost of the battery, which is not conducive to the commercial application of the electrolyte. Local high-concentration electrolyte is to add diluents such as fluoroethers to high-concentration electrolytes to reduce the concentration while keeping the local solvation structure similar. The diluent itself has a similar or wider electrochemical window as the high-concentration electrolyte, is insoluble in salt, but is miscible with the solvent to form an (ion-solvent) diluent state. Chinese patent CN 116231084 A discloses a high-voltage sodium ion battery electrolyte, which uses a highly fluorinated ether compound (such as TTE, HFE) solvent with low polarity to weaken the interaction between sodium ions and solvent molecules, thereby accelerating the desolvation of sodium ions at the electrode interface; in addition, the diluent can increase the local concentration, so that an excellent CEI is formed at the interface, thereby achieving a long cycle of the battery. The electrolyte obtained by this invention has good compatibility with the layered oxide positive electrode and the sodium metal negative electrode, and overcomes the problem of continuous decomposition of the conventional sodium ion battery electrolyte and interface, which is beneficial for the sodium ion battery to have good cycle performance and rate performance under high-voltage working conditions. Summary of the invention
[0006] The present invention proposes an electrolyte suitable for sodium ion batteries using phosphate materials as positive electrode active materials, which has the characteristics of high conductivity, low cost, dense and stable interface layer, and good electrical insulation between electrodes and electrolytes, and is particularly suitable for use in sodium ion batteries with a discharge platform higher than 4V. The details are as follows:
[0007] A sodium ion battery electrolyte, comprising a conductive sodium salt, an organic solvent and a composite additive, wherein the composite additive comprises nitriles, sulfonates and organic sodium salts, and the total mass concentration of the additive in the electrolyte is 2wt%-10wt%;
[0008] The organic sodium salt is sodium bis(trifluoromethyl)sulfonyl imide, and its concentration in the electrolyte is 0.2-2%;
[0009] The sulfonate additive is one of propenyl-1,3-sultone, 1,3-propanesultone (PS), propenyl-1-methyl-1,3-sultone, propenyl-1-ethyl-1,3-sultone, butenyl-1,4-sultone, butenyl-1-methyl-1,4-sultone, butenyl-1-ethyl-1,4-sultone, and its concentration is 0.5-5%;
[0010] The nitrile additive is a straight-chain dinitrile with two C≡N functional groups located at both ends of the molecule, and the general molecular structure is C n H 2n-4 N2, n is a positive integer, 3≤n≤6, and its concentration in the electrolyte is 0.2-3%.
[0011] The organic solvent is a carbonate compound, and the carbonate is a mixture of cyclic carbonate and chain carbonate, wherein the volume percentage of the chain carbonate in the organic solvent is 20%-80%.
[0012] The cyclic carbonate is one of ethylene carbonate and propylene carbonate or a mixture of the two.
[0013] The chain carbonate is one of diethyl carbonate, dimethyl carbonate or ethyl methyl carbonate.
[0014] The conductive sodium salt is soluble in the organic solvent and includes one of sodium hexafluorophosphate, sodium perchlorate and sodium tetrafluoroborate, and the total concentration of the sodium salt is 0.5-1.5M.
[0015] The preparation method of the sodium ion battery electrolyte is as follows: in an argon-protected glove box, the additive and the sodium salt are added to the organic solvent in sequence, stirred and mixed, and after all the solid substances are completely dissolved and stirred evenly, a molecular sieve is added to the electrolyte to remove water.
[0016] The water content in the electrolyte should be lower than 10 ppm.
[0017] The electrolyte is used as a high-voltage electrolyte in sodium ion batteries. The high-voltage electrolyte refers to a battery with a charging upper limit cutoff voltage range of 4.3 to 4.6V.
[0018] The positive electrode active material of the sodium ion battery is a phosphate-based sodium salt, including sodium vanadium phosphate (Na3V2(PO4)3), sodium vanadium fluorophosphate (Na3V2(PO4)2F3), sodium vanadium iron phosphate (Na3VFe(PO4)3), sodium vanadium manganese phosphate (Na3VMn(PO4)3), sodium vanadium chromium phosphate (Na3VCr(PO4)3), composite sodium iron manganese phosphate (Na4FeMn(PO4)P2O7) and one of the sodium salts doped with heterovalent ions of the above materials.
[0019] The electrolyte can generate a dense SEI layer rich in various inorganic components, which can ensure the Na + The rapid diffusion of ions and the appropriate reduction of the organic content in SEI improve the stability of SEI during long-term cycling. The capacity retention rate of sodium ion batteries assembled with phosphate materials as positive electrode active materials is greater than 80% after 1000 cycles at 1C rate.
[0020] The present invention has the following beneficial effects:
[0021] 1. Adding organic sodium salt NaTFSI additives to the electrolyte can generate a SEI layer rich in various inorganic components, which can ensure Na + The diffusion of ions, while appropriately reducing the organic content in SEI, improves the stability of SEI during long-term cycling. Studies have found that the anions of the electrolyte salt control the overall properties of the SEI layer formed on the negative electrode, including the composition and depth distribution of the substances in the SEI. The SEI on the sodium-carbon material contains organic and inorganic substances, which are obtained by the degradation of the electrolyte solvent and the salt anions, respectively. The inorganic layer is dense and stable, usually in close contact with the negative electrode, while the organic layer is a gel-like outer layer of the polymer network, close to the electrolyte side, with poor stability, and many components can be dissolved in the electrolyte. For example, an article reported that the dissolution order of SEI components in the electrolyte is Li2EDC>LiOCO2CH3>LiOH>LiOCO2C2H5>LiOCH3>LiF>[LiCO2]2>Li2CO3>Li2O. Therefore, SEI rich in inorganic components is more conducive to inhibiting electrolyte decomposition and related parasitic reactions. In commonly used ester electrolytes, the main solvent (such as cyclic carbonate EC, PC, etc.) is very polar and has strong contact with Na + Strong coordination occurs, resulting in the anion (PF6 - ) and Na + The coordination between them is weak, Na + PF6 in the solvation layer - The share is very small, and the free PF6 - Due to the repulsive force of the electric field, it is difficult to enter the double electric layer on the negative electrode surface, resulting in a small amount of NaF generated by NaPF6 on the negative electrode surface. + With TFSI - The ionic coordination between anions is strong, TFSI - Anions can enter Na +In the solvation shell, an electrochemical reduction reaction occurs at the negative electrode to generate a dense layer rich in various inorganic components such as Na3N, NaF, Na2O, and Na2SO3, while reducing the number of coordinated solvent molecules in the solvation layer and appropriately reducing the content of organic matter in SEI.
[0022] 2. The combination of sulfonic acid esters with unsaturated double bonds and nitrile additives can form a protective interface layer on the positive and negative electrode surfaces of sodium ion batteries. The N atom of C≡N in the nitrile molecular structure has a lone pair of electrons. The surface of the positive electrode material in the discharge state lacks electrons. Under the action of the electric field, the nitrile molecules are easily adsorbed and oxidized on the positive electrode surface (3.6V vs. Na + / Na) to generate CEI, electrically insulating the main solvent (carbonate) from the positive electrode surface, thereby preventing electrochemical oxidation of the main solvent and improving the stability of the battery. However, nitrile molecules are repelled by the negative electrode electric field and will not form an effective interface layer on the negative electrode surface. Sulfonic acid esters with unsaturated double bonds have a higher reduction potential and can undergo a reduction reaction at a higher potential to generate a dense inorganic layer (Na2O, Na2SO3, etc.), which effectively blocks the electrical contact between the electrolyte and the negative electrode surface, thereby improving the electrolyte's anti-reduction ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The cycling stability of the sodium ion soft-pack full battery assembled with the electrolyte of Example 1 at a rate of 1C. The voltage window is 2-4.6V, the upper limit cut-off voltage of the charge is 4.6V, and the charging mode is constant current + constant voltage.
[0024] Appendix Description
[0025] Appendix 1 lists the sodium ion battery embodiments of the present invention, electrolyte composition and positive electrode active material correspondence table.
[0026] Appendix 2 is a table showing the correspondence between sodium ion battery examples and capacity retention rates after 1000 cycles at 1C. DETAILED DESCRIPTION
[0027] The technical solution of the embodiment of the present invention is further described below through examples.
[0028] Example 1
[0029] 1. The preparation process of sodium ion battery electrolyte is as follows:
[0030] Prepare electrolyte #1 in an argon-protected glove box. NaPF6 is used as sodium salt, the concentration of NaPF6 is 0.5M, and the mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) is used as organic solvent, with a volume ratio of 1:1; the additives are composed of NaTFSI, malononitrile (MN), and propenyl-1,3-sultone (PST). The mass concentration of each component in the electrolyte is shown in Table 1.
[0031] The additive and sodium salt were added to the organic solvent and stirred to mix. After all the solid substances were completely dissolved and stirred evenly, molecular sieves were added to the electrolyte to remove water. The water content was tested to be 6.5 ppm.
[0032] 2. Assembly and cycle stability test of sodium ion batteries
[0033] The positive electrode sheet is prepared as follows: homemade sodium vanadium phosphate (NVP) is used as the active material, and the active material (NVP): conductive agent (super P): binder (polyvinylidene fluoride (PVDF)) is mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is used as a dispersant to prepare a slurry, which is coated on the surface of double-sided carbon-coated aluminum foil and dried to form a positive electrode sheet. In this embodiment, the coating surface density of the positive electrode is 15 mg cm -2 .
[0034] The preparation of the negative electrode sheet is as follows: biomass hard carbon (HC) is used as the negative electrode active material. The active material (HC): conductive agent (super P): binder (sodium carboxymethyl cellulose CMC) are mixed in a mass ratio of 92:4:4, and deionized water is used as a dispersant to prepare a slurry, which is coated on the surface of aluminum foil and dried to form a negative electrode sheet. The coating surface density of the negative electrode is calculated according to the negative electrode / positive electrode capacity ratio (N / P ratio) of 1.02. Battery assembly and performance testing: In an environment with a dew point ≤-20, a polyethylene film (PE type, model SK12) prepared by a wet method is used as a battery separator to assemble a 4 positive and 5 negative sodium ion soft pack battery with an effective area of 78cm 2 Then, it was assembled with the electrolyte prepared in 1 above, with the injection volume of 6g. After the assembly was completed, the steps of packaging, shelving, formation, secondary packaging, etc. were carried out to obtain the sodium ion battery 1# based on NVP. After the capacity was divided at room temperature (0.2C), the charge and discharge cycle test at a rate of 1C was carried out. The discharge capacity of the first cycle was recorded as C dc-1 , the cycle test is 1000 cycles, and the discharge capacity of the 1000th cycle is recorded as C dc-1000 , the capacity retention rate of 1C rate cycle is calculated according to formula (1). The electrochemical window of the cycle test is 2V~4.6V, and the test mode is constant rate + constant voltage, where the cutoff condition of 4.6V constant voltage is rate ≤0.05C.
[0035] 1C capacity retention rate (%) = C dc-1000 ×100% / C dc-1 (1)
[0036] During the charging process of sodium-ion batteries using ester-based electrolytes, as the amount of sodium stored in the negative electrode continues to increase, the negative electrode potential gradually shifts negatively, and the components with lower LUMO values in the electrolyte in contact with the negative electrode undergo electrochemical reduction reactions, generating inorganic substances including sodium carbonate (Na2CO3) and organic solid substances such as alkyl sodium carbonate (RCO3Na) and alkyl sodium alcohol (RONa) that are deposited on the surface of the negative electrode to form SEI, while consuming Na from the positive electrode. + SEI "electrically isolates" the electrolyte from the negative electrode to prevent the electrolyte from being consumed by continuous electrochemical reactions. + The negative electrode potential gradually increases as the negative electrode potential increases to above 0.7 V. Some organic components in the SEI, such as RONa, will undergo electrochemical dissolution, causing the SEI to become rough and loose, and the "electrical isolation" effect on the electrolyte will also deteriorate.
[0037] At the positive electrode, as the charging process proceeds, Na + It escapes from the lattice of the positive electrode active material, the positive electrode potential increases, and the components with higher HOMO values in the electrolyte in contact with the positive electrode will undergo electrochemical oxidation reaction. The higher the upper cut-off voltage, the higher the potential of the positive electrode, and the more violent the oxidation reaction of the electrolyte in contact with the positive electrode will be.
[0038] In this embodiment, Na of the organic sodium salt NaTFSI is + With TFSI - The ionic coordination between anions is strong, TFSI - Anions can enter Na + During battery charging, TFSI - The anions undergo electrochemical reduction reactions to generate dense layers rich in various inorganic components such as Na3N, NaF, Na2O, and Na2SO3, while reducing the number of coordinated solvent molecules in the solvation layer and the content of organic matter in SEI. In the subsequent discharge process, as the sodium removal process proceeds, these inorganic components will not undergo electrochemical oxidation and dissolution as the negative electrode potential gradually increases, thereby ensuring the "electrical isolation" of SEI from the electrolyte.
[0039] In addition, the combination of sulfonic acid esters with unsaturated double bonds and nitrile additives can form a protective interface layer on the positive and negative electrode surfaces of sodium ion batteries. The N atom of C≡N in the nitrile molecular structure has a lone pair of electrons. The surface of the positive electrode material in the discharge state lacks electrons. Under the action of the electric field, the nitrile molecules are easily adsorbed and oxidized on the positive electrode surface (3.6Vvs.Na+ / Na) to generate CEI, electrically insulating the main solvent (carbonate) from the positive electrode surface, thereby preventing electrochemical oxidation of the main solvent and improving the stability of the battery. However, nitrile molecules are repelled by the negative electrode electric field and will not form an effective interface layer on the negative electrode surface. Sulfonic acid esters with unsaturated double bonds have a higher reduction potential and can undergo a reduction reaction at a higher potential to generate a dense inorganic layer (Na2O, Na2SO3, etc.), which effectively blocks the electrical contact between the electrolyte and the negative electrode surface, thereby improving the electrolyte's anti-reduction ability.
[0040] Based on the above analysis, it can be seen that the combination of three additives, namely sulfonates with unsaturated double bonds, nitriles and organic sodium salts NaTFSI, can construct a high-density interface layer at both the positive and negative electrodes of the sodium-ion battery, thereby providing a guarantee for the battery to operate at a higher upper charge cutoff voltage and a wider electrochemical window.
[0041] The calculation results in Table 2 show that the battery using the electrolyte of the embodiment of the present application has a high capacity retention rate, and the capacity retention rate of 1000 cycles at a rate of 1C is greater than 80%, indicating that the corresponding formula electrolyte provided by the present invention can provide stable operation for the sodium ions assembled by the phosphate-based positive electrode material, in particular, under the conditions of charging voltage ≥4.3V and discharging voltage ≥2V, the electrochemical oxidation and electrochemical reduction reactions of the main solvent on the surface of the positive and negative electrodes can be suppressed, thereby providing a guarantee for the safety of the battery.
[0042] Embodiments 2 to 9
[0043] The electrolytes are numbered 2# to 9#, respectively. The composition and positive electrode active materials of the assembled battery are detailed in Table 1. The negative electrode, battery assembly, test mode, etc. used are the same as in Example 1. The electrochemical window of the cycle test is shown in Table 2.
[0044] Appendix 1 Sodium ion battery examples, electrolyte composition and positive electrode active material correspondence table
[0045]
[0046] explain:
[0047] In the electrolyte composition expressions in Table 1, the letter "v" represents the volume ratio of each solvent component in the electrolyte; the symbol "%" represents the mass percentage of the additive in the electrolyte; and the letter "M" represents the molar concentration of the sodium salt in the electrolyte.
[0048] For example, the expression of the electrolyte composition of Example 1-1# EC:DEC=1:1(v) / / 2%PST / 0.5%MN / 0.5%NaTFSI / 0.5M NaPF6 means that the electrolyte composition is: the volume ratio of EC:DEC is 1:1, the mass percentage of the additive PST (propenyl-1,3-sulfonate) is 2%, the mass percentage of MN (malononitrile) is 0.5%, the mass percentage of the organic sodium salt NaTFSI is 0.5%, and the molar concentration of NaPF6 is 0.5M.
[0049] Appendix 2: Capacity retention rate of sodium ion battery examples and 1C cycles for 1000 times
[0050] Example No. Electrochemical Window 1C cycle 1000 times CR / % Example 1 2V~4.6V 87 Example 2 2V~4.3V 90 Example 3 2V~4.3V 88 Example 4 2V~4.5V 86 Example 5 1.5V~4.3V 83 Example 6 2V~4.5V 85 Example 7 2V~4.6V 88 Example 8 2V~4.3V 82 Example 9 1.5V~4.3V 84 Comparative Example 1 2V~4.6V 71 Comparative Example 2 2V~4.3V 74 Comparative Example 3 1.5V~4.3V 62 Comparative Example 4 2V~4.5V 64 Comparative Example 5 2V~4.5V 54 Comparative Example 6 2V~4.5V 56 Comparative Example 7 2V~4.5V 69
[0051] The calculation results in Table 2 show that the battery using the electrolyte of the embodiment of the present application has a high capacity retention rate, and the capacity retention rate of 1000 cycles at a rate of 1C is greater than 80%, indicating that the corresponding formula electrolyte provided by the present invention can provide stable operation for the sodium ions assembled by the phosphate-based positive electrode material, in particular, under the conditions of charging voltage ≥4.2V and discharging voltage ≥2V, the electrochemical oxidation and electrochemical reduction reactions of the main solvent on the surface of the positive and negative electrodes can be suppressed, thereby providing a guarantee for the safety of the battery.
[0052] In Comparative Example 1, the concentration of sodium salt as ion conduction is 1.8M, which is close to the upper limit of solubility in ester electrolyte, resulting in excessive viscosity of electrolyte. + The migration rate of Na is low. In the high-rate cycle of 1C, the low-conductivity electrolyte is not enough to provide sufficient Na + , which leads to higher electrochemical polarization and continuous attenuation of battery performance. The sodium salt concentration in Comparative Example 5 is only 0.3M, and the Na + The number is small and it cannot provide sufficient Na to the electrochemical reaction interface during high-rate cycling. + , which leads to higher electrochemical polarization and continuous deterioration of battery performance.
[0053] In Comparative Example 2, the concentration of the unsaturated sulfonic acid ester was 8%. Due to the formation of a thick interface layer on the negative electrode surface, Na + The migration path is too long, and its higher interfacial resistance will also cause high electrochemical polarization, which is not conducive to the stable output of battery performance.
[0054] In the electrolytes of Comparative Examples 3, 4 and 6, the amounts of unsaturated sulfonate, NaTFSI and nitrile additives used are all lower than the concentration range given in the present invention. Since the content of inorganic salts (such as NaF, Na2S, Na2SO3, Na3N, etc.) in the interface layer is low, it is not enough to form an effective dense inner layer on the electrode surface, so that the electrolyte and the electrode cannot be effectively electrically insulated, and the main solvent will continue to undergo electrochemical decomposition, resulting in low battery stability. The capacity retention rate after 1000 cycles at a 1C rate is less than 70%, which cannot meet practical requirements.
[0055] In Comparative Example 7, the concentration of nitrile additives is relatively high, and the cycle stability of the battery is poor. The main reason is that the additives in the electrolyte cannot form an effective SEI barrier layer at the negative electrode. The adsorption of high concentrations of nitrile molecules on the negative electrode surface repels the unsaturated sulfonate molecules from approaching the negative electrode surface, resulting in a small number of reduced molecules of the latter on the electrode surface, which is insufficient to form an effective dense inorganic layer, and cannot effectively insulate the electrolyte from the electrode. The main solvent will continue to undergo electrochemical decomposition, and the battery cannot be stably charged and discharged.
[0056] As described above, these are merely embodiments of the present application. The protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application.
Claims
1. A sodium ion battery electrolyte, characterized in that: The electrolyte comprises sodium salt, organic solvent and additives, wherein the additives comprise nitriles, unsaturated sulfonic acid esters and organic sodium salts. The organic sodium salt is sodium bis(trifluoromethyl)sulfonyl imide, and its mass concentration in the electrolyte is 0.2-2%, preferably 0.3-1.8%; The unsaturated sulfonate additive is one or more of propenyl-1,3-sultone, propenyl-1-methyl-1,3-sultone, propenyl-1-ethyl-1,3-sultone, butenyl-1,4-sultone, butenyl-1-methyl-1,4-sultone, butenyl-1-ethyl-1,4-sultone, and the mass concentration thereof in the electrolyte is 0.5-5%, preferably 1-4%; The nitrile additive is one or more of the linear dinitriles, and the two C≡N in the linear dinitriles are located at both ends of the molecule, and the molecular structure is C n H 2n-4 N2, n is a positive integer, 3≤n≤6, and its mass concentration in the electrolyte is 0.2-3%, preferably 0.25-2.5%.
2. The sodium ion battery electrolyte according to claim 1, characterized in that: The linear dinitrile is specifically one or more of malononitrile, succinonitrile, glutaronitrile and adiponitrile.
3. The sodium ion battery electrolyte according to claim 1, characterized in that: The total mass concentration of the additives in the electrolyte is 2wt%-10wt%, preferably 3-9%.
4. The sodium ion battery electrolyte according to claim 1, characterized in that: The organic solvent is a carbonate compound, and the carbonate is a mixture of cyclic carbonate and chain carbonate, wherein the volume percentage of the chain carbonate in the organic solvent is 20%-80%, preferably 30-70%.
5. The sodium ion battery electrolyte according to claim 4, characterized in that: The cyclic carbonate is one of ethylene carbonate and propylene carbonate or a mixture of the two; The chain carbonate is one or more of diethyl carbonate, dimethyl carbonate or ethyl methyl carbonate.
6. The sodium ion battery electrolyte according to claim 1, characterized in that: The sodium salt is soluble in the organic solvent, including one of sodium hexafluorophosphate and sodium perchlorate, and the total concentration of the sodium salt is 0.5-1.5M, preferably 0.6-1.2M.
7. A method for preparing a sodium ion battery electrolyte according to any one of claims 1 to 6, characterized in that: In an argon-protected glove box, the additive and sodium salt are added to an organic solvent, and the mixture is stirred and mixed. After all solid substances are completely dissolved and stirred evenly, a molecular sieve is added to the electrolyte to remove water; The water content in the electrolyte is equal to or lower than 10 ppm.
8. An electrolyte as claimed in any one of claims 1 to 7 is used as a high-voltage electrolyte in a sodium ion battery.
9. The use according to claim 8, characterized in that The positive electrode active material of the sodium ion battery is a phosphate-based sodium salt, including sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium vanadium iron phosphate, sodium vanadium manganese phosphate, sodium vanadium chromium phosphate, composite sodium manganese iron phosphate, and one of the sodium salts doped with heterovalent ions of the above materials.
Citation Information
Patent Citations
High-voltage-resistant sodium-ion battery electrolyte as well as preparation method and application thereof
CN116231084A
Electrolyte, preparation method thereof and lithium ion battery
CN113471539A
Secondary battery
CN114464887A
Flame-retardant electrolyte for sodium ion battery and sodium ion secondary battery
CN115706263A
Electrolyte and electrochemical device comprising the same
US20220115695A1